A CO2-mediated base catalysis approach for the hydration of triple bonds in ionic liquids. Issue 24 (24th November 2021) - Tang, Minhao; Zhang, Fengtao; Zhao, Yanfei; Wang, Yuepeng; Ke, Zhengang; Li, Ruipeng; Zeng, Wei; Han, Buxing; Liu, Zhimin
Abstract : CO2 mediates ILs to serve as base catalysts for the activation of triple bonds, which achieves hydration of nitriles and CC containing compounds to carbonyl compounds under metal-free conditions. Abstract : Herein, we report a CO2 -mediated base catalysis approach for the activation of triple bonds in ionic liquids (ILs) with anions that can chemically capture CO2 ( e.g., azolate, phenolate, and acetate), which can achieve hydration of triple bonds to carbonyl chemicals. It is discovered that the anion-complexed CO2 could abstract one proton from proton resources ( e.g., IL cation) and transfer it to the CN or CC bonds via a six-membered ring transition state, thus realizing their hydration. In particular, tetrabutylphosphonium 2-hydroxypyridine shows high efficiency for hydration of nitriles and CC bond-containing compounds under a CO2 atmosphere, affording a series of carbonyl compounds in excellent yields. This catalytic protocol is simple, green, and highly efficient and opens a new way to access carbonyl compounds via triple bond hydration under mild and metal-free conditions.